Hump‐Inspired Hierarchical Fabric for Personal Thermal Protection and Thermal Comfort Management. (15th January 2023) - Xu, Duo; Chen, Ze; Liu, Yingcun; Ge, Can; Gao, Chong; Jiao, Longan; Guo, Weiqi; Zhang, Qian; Fang, Jian; Xu, Weilin
Abstract: Personal protection is critical for firefighters to ensure their safety in an extreme fire environment. However, conventional firefighter uniforms tend to focus on thermal protection and have the bottleneck of lacking personal thermal management. The heat stress caused by poor thermal management inevitably detriments human body health. Here, a hump‐inspired hierarchical fabric (HHF) composed of hierarchical insulation structure and directional water transport is demonstrated for personal thermal protection and thermal comfort management. The results show that the HHF exhibits enhanced thermal insulation ability and endows continuous one‐way liquid flow through distributed sweat‐wicking channels. Compared to conventional firefighter uniform fabrics, HHF shows simultaneously low thermal conductivity (0.0192 W m −1  K −1 ) in the cross‐plane direction and high breathability and moisture permeability. It is observed that the temperature and relative humidity of the simulated skin covered‐HHF uniform at extreme condition (≈80 °C) are ≈20.6 °C and ≈13.6% lower than that of conventional firefighter uniforms. It is expected that the HHF fabric with exceptional thermal performance can make a significant impact on future development of advanced protection uniform for firefighters. Abstract : A hump‐inspired hierarchical fabric (HHF) composed of a hierarchical insulation structure and directional water transport is developed for personal thermal protection and thermal comfort management. The prepared HHF shows superior thermal insulation ability, breathability, and moisture permeability. The temperature and relative humidity under HHF at extreme condition (≈80 °C) are ≈20.6 °C and ≈13.6% lower than conventional firefighter uniforms.